De la survisibilité/invisibilité sociale à la colère politique - Pauline Vermeren (Terrains/Théories)
Starting from the forms of invisibilization of people perceived as black in the narratives of Ralph Ellison and Richard Wright, this article proposes to reflect on the link between invisibility, overvisibility and social recognition. This allows us to introduce the link between social invisibility and epistemic invisibilization in the face of the proposal of a critical and decolonial phenomenology reconfiguring the political field of the sensible traversed by the affect of anger. This tragic “game” between ontological survisibility and social invisibility contains a sharing of the sensible that characterizes a global political history of race and racism. It involves processes of epistemic invisibilization, i.e. the erasure of existences, through their productions, traces and memories, or their occultation as actors in contexts where their roles have been socially, politically and historically decisive – resistance, independence, emancipation. This work contributes to questioning the production of philosophical knowledge and its responsibility for the link between epistemic invisibility and social invisibility, regarding the disappearance of black bodies from spaces of power and knowledge, relegating them to its margins in a “zone of non-being”, according to Fanon’s expression, and without a history of their own. This article defends the idea that there can be no analysis of a condition of existence without linking it to the political conditions of production of this knowledge.